Biophysical limits to global food production - Penning de Vries, Frits W. T.; Van Keulen, H.; Rabbinge, R.; Luyten, J. C. (International Food Policy Research Institute, 1995)
Global food production, so far, has increased continuously because cropped area has expanded and productivity per unit area has increased. In some regions of the world, however, there is little scope for further spatial expansion of agriculture. In other areas, crop yields are stagnating. Does this imply that the world is approaching the biophysical limits of food production? In this research nine food-demand scenarios were analyzed, ranging from minimum population growth combined with a vegetarian diet to maximum population growth combined with an affluent diet containing an ample amount of animal products. With an environment-oriented agriculture, all regions can produce the food required even for an affluent diet, except for East, South, and Southeast Asia; the three regions with the least leeway will carry almost half of the global population. West Asia and West and North Africa come close to the lower limit. A much less expensive diet provides the only option for escape, apart from massive food imports. Europe, the former U.S.S.R., North America, Oceania, South America, and Central Africa are well-off and need only part of their suitable land to feed their populations whatever their diet. However, if trade can distribute food efficiently across the globe, all people may consume an affluent diet, but at the expense of intensive use of two-thirds of the globe for arable crops and rangeland.